Accuracy of panoramic radiography in diagnosing maxillary sinus-root relationship: A systematic review and meta-analysis - Sun, Wentian (Angle Orthod, 2018)
OBJECTIVE: To investigate the accuracy of panoramic radiography (PR) in diagnosing maxillary sinus-root relationships (SRRs). MATERIALS AND METHODS: PubMed, EMBASE, CENTRAL, Web of Science, ScienceDirect, CBM, Baidu Scholar, and SIGLE were searched. The studies comparing the diagnostic accuracy of PR and computed tomography/cone-beam computed tomography (CT/CBCT) for SRR were included. RESULTS: Eleven studies were included. Meta-analyses showed that, for type I SRR, PR had the highest specificity, positive likelihood ratio (+LR), diagnostic odds ratio (DOR), and area under the curve (AUC), with a high sensitivity and a low negative LR (−LR). For type IV, PR had a high DOR and AUC, with the highest sensitivity but a low +LR, the lowest –LR, and the lowest specificity. For type II, PR had the lowest AUC, with a low sensitivity, +LR, and DOR and a high −LR. For type III, PR had the lowest sensitivity, +LR, and DOR and the highest −LR. The distance from root tips to the maxillary sinus floor on PR was significantly longer (mean difference: −1.88 mm; 95% confidence interval: −2.19 to −1.57; P < .0001) than that on CT/CBCT. CONCLUSIONS: Currently available evidence suggests PR could be reliable for detecting type I SRR. PR has a good ability to confirm true type IV SRR but a poor ability to rule out false type IV SRR. For type II and III SRR, PR shows poor accuracy and tends to overestimate the extent of protrusion of the roots into the maxillary sinus. When PRs display type II, III, or IV SRR and related treatment is needed, CBCT should be used for further examinations.